Tool use moves the peri-personal space from the hand to the tip of the tool - Saneyoshi, Ayako; Takayama, Ryota; Michimata, Chikashi (Frontiers in Psychology, 2023)
In this study, we used a visual target detection task to investigate three hypotheses about how the peri-personal space is extended after tool-use training: Addition, Extension and Projection hypotheses. We compared the target detection performance before and after tool-use training. In both conditions, the participants held a hockey stick-like tool in their hand during the detection task. Furthermore, we added the no-tool holding condition to the experimental design. In the no-tool holding condition, a peri-hand space advantage in the visual target detection task was observed. When the participants held the tool with their hand, this peri-hand space advantage was lost. Furthermore, there was no peri-tool space advantage before tool training. After tool training, the peri-tool space advantage was observed. However, after tool training, the advantage of the peri-hand space was not observed. This result suggested that the peri-hand advantage was reduced by simply holding the tool because the participants lost the functionality of their hand. Furthermore, tool-use training improved detection performance only in the peri-tool space. Thus, these results supported the projection hypothesis that the peri-personal space advantage would move from body to the functional part of the tool.